Issues of Human Resource Management 2017
DOI: 10.5772/67868
|View full text |Cite
|
Sign up to set email alerts
|

Use of Psychological Examinations of Employees and Job Applicants in Personnel Management

Abstract: This paper deals with psychological and diagnostic examination of the personality of employees and candidates for work, an unexplored subject in the ield of labour law and human resource (HR) management in Slovakia. Based on legal analysis of national and international laws and regulations as well as medical knowledge in clinical and occupational psychology, the authors surveyed employers in various industry sectors to test several hypotheses. The results of this study and other empirical data are the foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…There has been a rise in the need to use psychometric tests in the recruitment process to select candidates. Different psychological factors affect the recruitment process of an employee in an organization (Olšovská and Švec, 2017). As reported by Cole et al (2009), recruiters look for candidates whose personality is in accord with the vacant position as it was found that personality largely impacts job performance.…”
Section: Selection Of Sales Personnelmentioning
confidence: 98%
See 1 more Smart Citation
“…There has been a rise in the need to use psychometric tests in the recruitment process to select candidates. Different psychological factors affect the recruitment process of an employee in an organization (Olšovská and Švec, 2017). As reported by Cole et al (2009), recruiters look for candidates whose personality is in accord with the vacant position as it was found that personality largely impacts job performance.…”
Section: Selection Of Sales Personnelmentioning
confidence: 98%
“…(Kidwell et al 2021, Chen andJaramillo, 2014). Olšovská and Švec (2017) stated that creativity is one of the main factors that recruiters look for in candidates. Creative people are more invested in their work as they look for novel solutions to different problems and it also encourages collaboration.…”
Section: Selection Of Sales Personnelmentioning
confidence: 99%
“…Psychometric tests reveal information about the candidate they did not intend to reveal themselves, and also provide information about the mental health of the candidate, the personality, ability to work under pressure etc. (Olšovská & Švec, 2017). If the purpose of the psychometric test is to gain information about the mental health of the candidate as a precondition to conduct particular work requires a specific legal regulation set out in Article 6 (1) (c) of the Regulation resp.…”
Section: Processing Of Information About the Physical And Mental Healmentioning
confidence: 99%
“…The scope of tasks is determined not only by the qualitative characteristics of the incentive system and the satisfaction of the primary needs of the employee. Essential are organizational means, monitoring and analysis of psychological features of professional motivation of personnel, focus on psychological methods of motivation management, understanding the dependence of individual effectiveness of the subject on the level of internal motivational readiness [14][15][16].…”
Section: Introductionmentioning
confidence: 99%